THE INFLUENCE OF JOB SATISFACTION AND COMPETENCY ON EMPLOYEES' JOB ACHIEVEMENT AT PT. NUSANTARA SURYA SAKTI - Kalsum, Eka Umi; Wijaya, Muslim (Accounting and Business Journal, 2023)
This research aims to determine the influence of job satisfaction and competence on employee work performance at PT. Nusantara Surya Sakti. The population in this study were employees of PT. Nusantara Surya Sakti with a sample size of 53 people. The data analysis model used is multiple linear regression analysis. The research method uses a quantitative descriptive approach supported by surveys, and is explanatory. The results of research using partial testing (t test) show that job satisfaction has a positive and significant effect on the work performance of employees PT. Nusantara Surya Sakti in Medan. Competency has a positive and significant effect on the work performance of employees. PT. Nusantara Surya Sakti . Furthermore, the results of the simultaneous test (F test) show that job satisfaction and competence have a positive and significant effect on the work performance of employees PT. Nusantara Surya Sakti. The coefficient of determination (R2) value of job satisfaction and competence is able to explain the work performance variable by 70.8% and the remaining 29.2% is influenced by other variables not examined in this research such as discipline, motivation, work environment and so on.